The role of transcription factors in the pathogenesis and therapeutic targeting of vascular diseases - Hu, Poyi; Du, Yifan; Xu, Ying; Ye, Ping; Xia, Jiahong (Frontiers in Cardiovascular Medicine, 2024)
Transcription factors (TFs) constitute an essential component of epigenetic regulation. They contribute to the progression of vascular diseases by regulating epigenetic gene expression in several vascular diseases. Recently, numerous regulatory mechanisms related to vascular pathology, ranging from general TFs that are continuously activated to histiocyte-specific TFs that are activated under specific circumstances, have been studied. TFs participate in the progression of vascular-related diseases by epigenetically regulating vascular endothelial cells (VECs) and vascular smooth muscle cells (VSMCs). The Krüppel-like family (KLF) TF family is widely recognized as the foremost regulator of vascular diseases. KLF11 prevents aneurysm progression by inhibiting the apoptosis of VSMCs and enhancing their contractile function. The presence of KLF4, another crucial member, suppresses the progression of atherosclerosis (AS) and pulmonary hypertension by attenuating the formation of VSMCs-derived foam cells, ameliorating endothelial dysfunction, and inducing vasodilatory effects. However, the mechanism underlying the regulation of the progression of vascular-related diseases by TFs has remained elusive. The present study categorized the TFs involved in vascular diseases and their regulatory mechanisms to shed light on the potential pathogenesis of vascular diseases, and provide novel insights into their diagnosis and treatment.